Official and private animal welfare inspectors’ perception of their own on-site inspections - Lundmark Hedman, Frida; Ewerlöf, Ivana R.; Frössling, Jenny; Berg, Charlotte (Frontiers in Veterinary Science, 2025)
The presence of a trustworthy and effective animal welfare control system is important both for animal welfare and for public and consumer trust. The inspectors’ main task, regardless of whether they are official inspectors or private auditors, is to check for and enforce compliance with any relevant regulations. The aim of this study was to investigate how official animal welfare inspectors and private animal welfare auditors in Sweden perceive their inspection work and to explore any differences in the perception of being an inspector between these two groups. An electronic questionnaire was developed and received responses from 108 official inspectors and 22 private auditors (mainly inspecting the KRAV standard, Arlagården®, and the Trotter Health Standard). The results show that the official inspectors and private auditors usually enjoy their work, and they quite often have similar ambitions and views on what characterizes a good inspector. The respondents stated, for example, that it is important to have good dialog with the inspected animal keeper, that it is important to make uniform assessments (even if this can be challenging to achieve), and that animal keepers quite often show their appreciation after an inspection. However, there were also a number of differences in perception between the groups. For example, the official inspectors felt more exposed to unpleasant and threatening situations, while the private auditors were more likely to report the keeper being expected as acting nicely, professionally and relaxed during routine inspections. The official inspectors had a slightly more negative attitude toward the presence of private auditors than the other way around. Nevertheless, the respondents were in agreement that their collaboration and communication needed to be improved. One should bear in mind that the official inspectors also carry out inspections after complaints and more often make unannounced inspections. They not only inspect farms and horse premises, as the private auditors do, they also inspect different pet premises and have a secondary position of power as representatives of the government compared to the private auditors. These various circumstances may partly explain different views and perceptions between the official inspectors and the private auditors.